Study on occurrence of agrochemical poisoning in Bovines at veterinary clinics of Udgir - KAKA, JADHAV RAVINDRA; UDHAVRAO, BHIKANE ANIL; GULAB, CHAVHAN SAMBHAJI (The Indian Journal of Animal Sciences, 2023)
In view of unavailability of data on agrochemical poisoning in livestock animals in India, the present work was conducted with objective to study the epidemiological aspects of agrochemical poisoning in bovines over a period of five years. A total of 98 cases of pesticide poisoning in bovines have been reported during 2016-2020 at Veterinary Clinical Complex, College of Veterinary and Animal Sciences, Udgir with hospital prevalence of 0.39%. Among various agrochemicals, insecticide poisoning was responsible for 45.91% cases, fungicide for 17.34%, herbicides for 16.32%, unknown pesticides for 10.20%, fertilizers for 7.14% and rodenticides for 3.06% cases of poisoning in bovines. Year-wise higher number of cases were reported during 2016 (30.61%) followed by 2017, 2019 (19.38% each) and 2018 (18.36%) while, month- wise highest number of poisoning cases were reported in months of November (14.28%), December (13.26%), July and September, October (11.22% each). Season-wise highest occurrence of poisoning was observed during monsoon and post-monsoon seasons while least occurrence was observed during summer season. Age-wise highest occurrence of agrochemical poisoning was reported in 4-6 year and 0-2 year age-group animals. Species-wise occurrence of poisoning revealed highest occurrence in cattle (65.31%) than buffaloes (34.69%). Among cattle 67.18% male animals while 32.82% female animals were affected. All buffaloes confirmed for poisoning were female. The findings of the present study will be helpful for formulating strategies to reduce exposure of livestock animals to agrochemicals.